2018
DOI: 10.3390/fib6030061
|View full text |Cite
|
Sign up to set email alerts
|

The Degradation of Cellulose by Radio Frequency Plasma

Abstract: This paper describes the results of using oxygen (O2) plasma to treat both greige and scoured cotton yarns to cause significant degradation of cellulose. This study is an effort to reduce hazardous caustic chemicals commonly used to make the cellulose molecule more accessible for uses in such applications as biofuels. Through high power density, 0.46 W/cm2, and the study of varying exposure times, we find longer durations of 30 min to 90 min result in significant cellulose structure degradation. Due to waxes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…This is likely attributed to the etching effect of highly energized plasma particles. Similar physical degradation was reported in several studies when fibers were exposed to oxygen plasma as well as DC air plasma and di-electric barrier discharge plasma (DBD) [ 49 , 52 , 53 , 54 ]. The presence of surface cracks and defects in plasma-pretreated cotton fibers could improve cellulose dissolution as they can facilitate solvent diffusion and accessibility to the internal well-organized structures of cellulose.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…This is likely attributed to the etching effect of highly energized plasma particles. Similar physical degradation was reported in several studies when fibers were exposed to oxygen plasma as well as DC air plasma and di-electric barrier discharge plasma (DBD) [ 49 , 52 , 53 , 54 ]. The presence of surface cracks and defects in plasma-pretreated cotton fibers could improve cellulose dissolution as they can facilitate solvent diffusion and accessibility to the internal well-organized structures of cellulose.…”
Section: Resultssupporting
confidence: 80%
“…Plasma pretreatment of cotton fibers for 20 and 40 min decreased the MW of cellulose by 36% (2.5 × 10 5 Da) and 60% (1.5 × 10 5 Da), respectively. Shepherd et al reported a similar effect of oxygen plasma treatment on the MW of cellulose [ 52 ]. The authors found that the initial level of polymer degradation was largely dependent on the level of impurities, such as wax substances, located on the sample surface.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A slight reduction of washing fastness for plasma treated fabrics was also reported by other authors (Akbarpour et al 2013;Feng et al 2020). Some research observed a physical degradation of the fabric after plasma treatment, such as microcracks pitting and splitting of the ber (Shepherd and Frey 2018;Feng et al 2020). These degraded bers were probably removed from the fabric during the washing and rubbing fastness tests.…”
Section: Colorfastness Propertiesmentioning
confidence: 99%
“…The surface etching by atmospheric plasma partially destroyed the hydrophobic layer and the hydrophilicity is dependent on the power and time of the plasma treatment (Carneiro et al 2001;Karahan and Özdoğan 2008). Shepherd and Frey (2018) treated scoured and greige cotton yarns with long plasma exposure times (15-90 min). Scoured cotton had severe physical damage, even at the lowest exposure time (15 min), while greige yarns had less degradation.…”
Section: Afm Analysismentioning
confidence: 99%